IMPA2 Downregulation Enhances mTORC1 Activity and Restrains Autophagy Initiation in Metastatic Clear Cell Renal Cell Carcinoma - Kuei, Chia-Hao; Lin, Hui-Yu; Lee, Hsun-Hua; Lin, Che-Hsuan; Zheng, Jing-Quan; Chen, Kuan-Chou; Lin, Yuan-Feng (Journal of clinical medicine, 2020)
Although mTOR inhibitors have been approved as first-line therapy for treating metastatic clear cell renal cell carcinoma (ccRCC), the lack of useful markers reduces their therapeutic effectiveness. The objective of this study was to estimate if inositol monophosphatase 2 (IMPA2) downregulation refers to a favorable outcome in metastatic ccRCC receiving mTOR inhibitor treatment. Gene set enrichment analysis predicted a significant activation of mTORC1 in the metastatic ccRCC with IMPA2 downregulation. Transcriptional profiling of IMPA2 and mTORC1-related gene set revealed significantly inverse correlation in ccRCC tissues. Whereas the enforced expression of exogenous IMPA2 inhibited the phosphorylation of Akt/mTORC1, artificially silencing IMPA2 led to increased phosphorylation of Akt/mTORC1 in ccRCC cells. The pharmaceutical inhibition of mTORC1 activity by rapamycin reinforced autophagy initiation but suppressed the cellular migration and lung metastatic abilities of IMPA2-silenced ccRCC cells. In contrast, blocking autophagosome formation with 3-methyladenine rescued the mitigated metastatic potential in vitro and in vivo in IMPA2-overexpressing ccRCC cells. Our findings indicated that IMPA2 downregulation negatively activates mTORC1 activity and could be a biomarker for guiding the use of mTOR inhibitors or autophagy inducers to combat metastatic ccRCC in the clinic.